On the origin of electrical conductivity in the bio-electronic material melanin - Paul Meredith (Applied Physics Letters, 2012)
The skin pigment melanin is one of a few bio-macromolecules that display electrical and photo-conductivity in the solid-state. A model for melanin charge transport based on amorphous semiconductivity has been widely accepted for 40 years. In this letter, we show that a central pillar in support of this hypothesis, namely experimental agreement with a hydrated dielectric model, is an artefact related to measurement geometry and non-equilibrium behaviour. Our results cast significant doubt on the validity of the amorphous semiconductor model and are a reminder of the difficulties of electrical measurements on low conductivity, disordered organic materials.